Diagnostic Performance of Adding the Optic Nerve Region Assessed by Optical Coherence Tomography to the Diagnostic Criteria for Multiple Sclerosis - Bsteh, Gabriel; Hegen, Harald; Altmann, Patrick; Auer, Michael; Berek, Klaus; Di Pauli, Franziska; Kornek, Barbara; Krajnc, Nik; Leutmezer, Fritz; Macher, Stefan; Rommer, Paulus Stefan; Zebenholzer, Karin; et al. (Neurology, 2023)
The optic nerve has been recommended as an additional region for demonstrating dissemination in space (DIS) in diagnostic criteria for multiple sclerosis (MS). The aim of this study was to investigate whether adding the optic nerve region as determined by optical coherence tomography (OCT) as part of the DIS criteria improves the 2017 diagnostic criteria. From a prospective observational study, we included patients with a first demyelinating event who had complete information to assess DIS and a spectral domain OCT scan obtained within 180 days. Modified DIS criteria (DIS + OCT) were constructed by adding the optic nerve to the current DIS regions based on validated thresholds for OCT intereye differences. Time to second clinical attack was the primary endpoint. We analyzed 267 patients with MS (mean age 31.3 years [SD 8.1], 69% female) during a median observation period of 59 months (range: 13-98). Adding the optic nerve as a fifth region improved the diagnostic performance by increasing accuracy (DIS + OCT 81.2% vs DIS 65.6%) and sensitivity (DIS + OCT 84.2% vs DIS 77.9%) without lowering specificity (DIS + OCT 52.2% vs DIS 52.2%). Fulfilling DIS + OCT criteria (≥2 of 5 DIS + OCT regions involved) indicated a similar risk of a second clinical attack (hazard ratio [HR] 3.6, CI 1.4-14.5) compared with a 2.5-fold increased risk when fulfilling DIS criteria (HR 2.5, CI 1.2-11.8). When the analysis was conducted according to topography of the first demyelinating event, DIS + OCT criteria performed similarly in both optic neuritis and nonoptic neuritis. Addition of the optic nerve, assessed by OCT, as a fifth region in the current DIS criteria improves diagnostic performance by increasing sensitivity without lowering specificity. This study provides Class II evidence that adding the optic nerve as determined by OCT as a fifth DIS criterion to the 2017 McDonald criteria improves diagnostic accuracy.